GE_GERICHTE P/16719/2014 vom 7. März 2016 - GE Cour de justice (2016)
DISPOSITIONS PÉNALES DE LA LCR; VIOLATION DES RÈGLES DE LA CIRCULATION; PEINE PÉCUNIAIRE; AMENDE; DÉPENS | LCR.90.2; CPP.436.2; CP.47; CP.42.4; CP.106